Comparison of sonodynamic, photodynamic and sonophotodynamic therapy activity of fluorinated pyridine substituted silicon phthalocyanines on PC3 prostate cancer cell line - Atmaca, Goknur Yasa; Aksel, Mehran; Bilgin, Mehmet Dincer; Erdogmus, Ali (ELSEVIER, 2023)
Background: Sonophotodynamic therapy (SPDT), a combination of photodynamic therapy (PDT) and sonody-namic therapy (SDT), may offer theraputic advantage. The therapeutic effects of sonodynamic, photodynamic, and sonophotodynamic of 5-(trifluoromethyl)-2-thiopyridine substituted silicon phthalocyanine (gy3) and its quaternized derivative (gy3q) were examined in vitro on prostate cancer using PC3 cells.Methods: The SDT, PDT and SPDT efficiency was determined by using MTT test.Apoptosis mechanism was evaluated by HOPI staining.Results and Discussions: According to MTT results, the phthalocyanines decreased cell viability when compared with a control group. Also, apoptosis measurement data represents that the phthalocyanines would produce much better therapeutic outcomes compare to PDT and SDT by utilizing SPDT. Further studies should be per -formed to understand the effectiveness of SPDT.
Keywords: Silicon phthalocyanine (SiPc); Photosensitizer; Photodynamic therapy; Sonophotodynamic therapy; Sonochemistry; DERIVATIVES; Oncology